Industrial R&D expenditure: its determinants and propensity of technology transfer of top ten companies in Malaysia, Singapore and Taiwan - Goh, Billy Kian Bing; Yee, Angelina Seow Voon; Kendall, Graham; Chong, Aik Lee (Hi-Tech Business Institute, Hannam University, 2017)
Global research and development (R&D) spending has increased in recent years as the need for new technologies has grown and structural changes in the market have become evident. R&D and its transfer into the commercial sector have an important relationship. This paper analyzes the relationship between industrial R&D expenditure and how it affects technology transfer in Malaysia, Singapore and Taiwan. The research is based on the analysis of secondary data from published annual reports followed by a quantitative analysis of primary data using survey questionnaires. The research finds that the bulk of R&D expenditure was from the top ten organizations and the top five industries for each country. The findings also reveal that an organization’s readiness in terms of technology and people capabilities is still weak in Malaysia and Singapore. The findings also indicate that there is a relationship between industrial R&D expenditure and the propensity of technology transfer in Taiwan.